Second-order parallel processing: visual search for the odd item in a subset. - Friedman-Hill, Stacia; Wolfe, Jeremy M. (Journal of Experimental Psychology. Human Perception & Performance, 1995)
Visual search tasks in which participants searched for an odd element in a subset of items were investigated. Participants searched for an item of odd orientation in the red subset. The target was a red line of X|Mo, distractors were green lines of X|Mo and red lines of Y|Mo. The orientations, X and Y, changed on every trial. In this task, orientation information was useful only after color had been used to select the relevant subset. Results show that response time (RT) and error data were different from standard color X orientation conjunction searches (Experiment 1). RT × Set Size functions had slopes near 0 ms per item (Experiment 2). The selection of the subset appeared to take 200–300 ms (Experiments 2 and 3). Subset selection was based on properties of the relevant subset, not the irrelevant subset (Experiment 4). It was more difficult (perhaps impossible) to select a subset defined by 2 colors (Experiment 5). Random variation in an irrelevant dimension did not disrupt subset search (Experiment 6). Reprinted by permission of the publisher.